Pengaruh Kebijakan Dividen, Leverage, Volume Perdagangan, Dan Nilai Tukar Rupiah Terhadap Harga Saham Khususnya Pada Sektor Consumer Goods Yang Tercatat Di Bursa Efek Indonesia - Ni Made Ayu Yulita Fridayanthi; Kadek Dewi Padnyawati; Putu Nuniek Hutnaleontina (Hita Akuntansi dan Keuangan, 2023)
Investment is an activity to invest in a company, with the hope of providing benefits in the future. To choosing a company, an investor needs to consider several things to determine his decision. This study aims to determine the effect of dividend policy, leverage, trading volume and exchange rate on stock prices. The population of this research is 66 non-cyclical consumer goods sector companies listed on the Indonesia Stock Exchange in the 2018-2020 period. The method of determining the sample used is the purposive sampling method, with several predetermined criteria, the samples is 27 companies in the non-cyclical consumer goods sector. The research data used is secondary data with multiple linear regression analysis techniques. The results show that dividend policy, leverage and trading volume have a significant effect on stock prices, while exchange rate have no significant effect on stock prices. Simultaneously dividend policy, leverage, trading volume and exchange rate affect stock prices